Comparison of Juday and WP2 nets used in joint Norwegian–Russian monitoring of zooplankton in the Barents Sea. (14th October 2019) - Skjoldal, Hein Rune; Prokopchuk, Irina; Bagøien, Espen; Dalpadado, Padmini; Nesterova, Valentina; Rønning, Jon; Knutsen, Tor
Abstract: Zooplankton in the Barents Sea has been monitored in a joint program by Norway and Russia using Juday (37 cm) and WP2 (56 cm) vertical plankton nets. We have compared the nets in two studies (2007 and 2013) with the Juday and WP2 nets mounted side by side on a common frame. WP2 collected consistently more zooplankton biomass than Juday, by 15–20% for both studies. Higher catch for small and medium size fractions as well as total biomass suggest that the difference was not due to extrusion or escape of organisms through the meshes, but rather that the amounts of flow and filtration of water through the two nets were different from the estimated volumes. Results for two hauling speeds (0.5 and 1.0 m s −1 ) in the 2013 study were not conclusive due to apparent changes in plankton composition at the sampling station during the study. The Juday and WP2 biomasses were highly correlated and the two nets showed very similar species composition with the pairwise design. The two nets would therefore give comparable spatial and temporal patterns of zooplankton distribution in the joint monitoring program.